University Lecturers’ Self-Efficacy in the Use of Edmodo for Teaching [Efikasi Diri Dosen-dosen Universitas dalam Penggunaan Edmodo untuk Mengajar] - Gboyega Ayodeji Aladesusi; Ayotunde A. Falade; Ojo Felix Oluwadare (Universitas Pendidikan Indonesia (UPI), 2022)
This study determined university lecturers’ self-efficacy in the use of Edmodo in Ekiti State. The study adopted descriptive research of the survey type. The population for this study was made up of all the lecturers in Ekiti- State. Proportional sampling techniques were used to allocate several respondents in each school based on their estimated population using Israel Model (2012). The instrument for data collection was an adapted questionnaire. Descriptive and Inferential statistics were used to answer the research question and test the stated hypothesis with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings indicated that the lecturer’s self-efficacy in the use of Edmodo for teaching is high. No significant difference exists in the lecturer’s self-efficacy in the use of Edmodo for teaching in Ekiti-State based on gender. The study concluded that learning can be enhanced and teaching can be effective among lecturers in Ekiti State if appropriate technologies are deployed for instruction. Therefore, it was recommended that Lecturers should be encouraged to deploy Edmodo for learning irrespective of their gender. Penelitian ini menentukan efikasi diri dosen universitas dalam penggunaan Edmodo di Ekiti-State. Penelitian ini mengadopsi penelitian deskriptif dengan tipe survei. Populasi penelitian ini adalah seluruh dosen di Ekiti-State. Teknik pengambilan sampel proporsional digunakan untuk mengalokasikan beberapa responden di setiap sekolah berdasarkan estimasi populasinya menggunakan Israel Model (2012). Instrumen yang digunakan untuk mengumpulkan data adalah angket yang diadaptasi. Statistik deskriptif dan inferensial digunakan untuk menjawab pertanyaan penelitian dan menguji hipotesis yang dikemukakan dengan bantuan Statistical Product and Service Solution (SPSS) versi 20.0 pada taraf signifikansi 0,05. Temuan menunjukkan bahwa efikasi diri dosen dalam penggunaan Edmodo untuk mengajar tinggi. Tidak ada perbedaan yang signifikan dalam efikasi diri dosen dalam penggunaan Edmodo untuk mengajar di Ekiti-State berdasarkan jenis kelamin. Studi ini menyimpulkan bahwa pembelajaran dapat ditingkatkan dan pengajaran dapat menjadi efektif di antara dosen di Ekiti-State jika teknologi yang tepat digunakan untuk pengajaran. Oleh karena itu, direkomendasikan agar dosen didorong untuk menggunakan Edmodo untuk pembelajaran terlepas dari jenis kelamin mereka.